A new species of Coccomyces from Guizhou Province of China - Zang, Wei; Lv, Tu; Sun, Jianqiu; Hou, Chenglin (Phytotaxa, 2020)
Specimens of Coccomyces collected from Fanjingshan National Nature Reserve in Guizhou Province of China were identified as a new species and named as Coccomyces fanjingshanensis. Phylogenetic analyses of the ITS gene and combined LSU and mtSSU genes indicate that this new taxon has a close relationship with Coccomyces huangshanensis, Coccomyces cupressinus and Coccomyces radiatus.The type collection was deposited in the Herbarium of the College of Life Science, Capital Normal University, Beijing, China (BJTC).